2018
DOI: 10.1002/2017ja025010
|View full text |Cite
|
Sign up to set email alerts
|

First Results From the Ionospheric Extension of WACCM‐X During the Deep Solar Minimum Year of 2008

Abstract: New ionosphere and electrodynamics modules have been incorporated in the thermosphere and ionosphere eXtension of the Whole Atmosphere Community Climate Model (WACCM‐X), in order to self‐consistently simulate the coupled atmosphere‐ionosphere system. The first specified dynamics WACCM‐X v.2.0 results are compared with several data sets, and with the Thermosphere‐Ionosphere‐Electrodynamics General Circulation Model (TIE‐GCM), during the deep solar minimum year. Comparisons with Thermosphere Ionosphere Mesospher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 73 publications
5
62
0
Order By: Relevance
“…Without ion drag, the wind circulation is much stronger and the day‐to‐night temperature difference is smaller. Recently, Liu et al () compared TIEGCM simulated ionospheric F 2 peak electron densities ( N m F 2 ) with COSMIC (the Constellation Observing System for Meteorology, Ionosphere, and Climate) observations and found that TIEGCM simulated N m F 2 values are significantly smaller than the observations during both day and night during the June solstice, consistent with other model‐data comparison studies (e.g., Lei et al, ; Qian et al, ). Thus, TIEGCM may underestimate the ion drag effect due to relatively low modeled N m F 2 values and produce larger winds than observations indicate in the summer.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Without ion drag, the wind circulation is much stronger and the day‐to‐night temperature difference is smaller. Recently, Liu et al () compared TIEGCM simulated ionospheric F 2 peak electron densities ( N m F 2 ) with COSMIC (the Constellation Observing System for Meteorology, Ionosphere, and Climate) observations and found that TIEGCM simulated N m F 2 values are significantly smaller than the observations during both day and night during the June solstice, consistent with other model‐data comparison studies (e.g., Lei et al, ; Qian et al, ). Thus, TIEGCM may underestimate the ion drag effect due to relatively low modeled N m F 2 values and produce larger winds than observations indicate in the summer.…”
Section: Discussionsupporting
confidence: 60%
“…Without ion drag, the wind circulation is much stronger and the day-to-night temperature difference is smaller. Recently, Liu et al (2018) compared TIEGCM simulated ionospheric F 2 peak electron densities (N m F 2 ) with COSMIC (the Constellation Observing System for Meteorology, Ionosphere, and Climate) observations and found that TIEGCM simulated N m F 2 values are significantly smaller than the observations during both day and night during the June solstice, consistent with other model-data comparison studies (e.g., Lei On the other hand, in the zonal direction, we find that TIEGCM-modeled WE winds in general have a larger speed at night at three stations, and that the reversal of wind direction from eastward to westward occurs at an earlier local time than the observed zonal winds from about March to August at XL and KL stations. This is consistent with overestimates of the equatorial meridional wind magnitude by the model in the same months.…”
Section: 1029/2018ja025424mentioning
confidence: 99%
“…Because at night, there is no significant ion production and molecular recombination is faster at low pressure levels (lower altitudes); the F 2 layer occurs at higher altitudes than during the daytime. Furthermore, the hmF 2 in the winter hemisphere is much lower than that in the summer hemisphere (Liu, Liu, Wang, et al, ). The peaks in the winter hemisphere disappear faster than that in the summer hemisphere (Abur‐Robb & Windle, ).…”
Section: Discussionmentioning
confidence: 99%
“…The WACCM‐X is a whole atmosphere model extending from the surface to the upper thermosphere (4.1 ×1em1010 hPa, 500–700 km) and includes necessary chemical, dynamical, and physical processes to model the whole atmosphere system. For a detailed description and validation of WACCM‐X, the reader is referred to Liu et al (, ). Simulations were performed as a free‐running climate simulation and are thus not representative of any specific year.…”
Section: Data and Modelsmentioning
confidence: 99%